Evaluating Indian Professionals Knowledge for Innovation and Need for Patent Education - Gupta, Sonu; Bansal, Ravinder Nath; Sodhi, Surender Pal Singh; Brar, Gursimrat Kaur (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2021)
The Patent system encourages invention, disclosure, and investment. Several patents are granted in medical sciences, but a misconception remains with health care professionals regarding criteria for patentability of their valuable invention. Though the Indian Patent system has promoted the progress of science and technology, its scope has not been extended to treatment procedures in medical and dental sciences. This research was conducted to assess the knowledge and awareness of health care professionals about the Indian patent system. The study was conducted to assess the awareness and knowledge of the Indian patent system and the need for patent education among professionals of different streams. This cross-sectional study was carried out among private practitioners of different streams (medical and dental, ayurvedic, and homeopathic). Results made a poor show of patent education and knowledge. Only 6% of participants had more than 50% knowledge regarding this topic. Since educational institutions are opting for accreditations. Research and innovation is an important criterion for that. This study highlighted that there is a great need for patent education for professional and institutional growth.